Membangun Rantai Pasok Anti Rapuh: Perspektif Pelaku UMKM - Diah Ayu Septi Fauji; Sudarmiatin Sudarmiatin; Agus Hermawan (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2022)
Building a strong and resilient supply chain is no longer enough to thrive in today's highly volatile business world. Therefore, this study aims to find ways to build an anti-fragile supply chain based on the perspective of SMEs in Kediri Regency. Using a qualitative case study method, this research investigates phenomena intensively and is practice-oriented in order to contribute experience to finding solutions in building an anti-fragile supply chain. The findings of the theme show that mastering the field, language, art of communication, establishing closeness with customers through interaction, reducing dependence on suppliers and willingness to grow in uncertainty and/or disruption are the keys for MSMEs to be able to build and manage an anti-fragile supply chain.